Topoanaliza autobiograficzno-symboliczna jako metoda badania (nie)dokończonych marzeń - Piasecka , Małgorzata (Studia Edukacyjne, 2020)
Piasecka Małgorzata, Topoanaliza autobiograficzno-symboliczna jako metoda badania (nie)dokończonych marzeń [Autobiographical-symbolic Topoanalysis as a Method of Examining (Un)Finished Dreams]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 401-419. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.22 The article is a presentation of an original research project on dreams. The author, being aware of the nature of dreams as the phenomena difficult to grasp empirically, tries to find a subtle way of describing them. The author does not take into account utopian dreams. On the contrary, she looks for real dreams experienced on the paths of life. Retaining the oneiric nature of dreams, she has constructed a research method and called it an autobiographical and symbolic topoanalysis. The construction of the method is preceded by an outline of the process of conceptualization, i.e. the adoption of appropriate theoretical background, conceptual instrumentation, and research strategy. The author assumes a spatial meta-order of analyses by pointing to a non-binary space, not fully decentralized, as a possible context of making dreams a reality. Important clues and assets from which she creatively draws are: the concept of M. Lanie-Bayle’s biographical space-time; the vestige et vertige concept, i.e. a trace and an inverted trace; the concept of the poetics of dreaming and the Four Elements by G. Bachelard; the concept of D. Demetrios’s autobiography; E. Rybicka’s geo-poetics in the contemporary literary discourse. Finally, the author describes the methodological stage of autobiographical and symbolic topoanalysis and presents a concrete example of its application.